PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TGT (TEAMS GAMES TOURNAMENT) DENGAN MEDIA QUESTION CARD DALAM MENINGKATKAN HASIL BELAJAR SISWA - Sari, Firda Fitdiyah Nikita; Aisyah, Iis; Srigustini, Astri (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
This research is based on the problems that occur at SMA Negeri 3 Tasikmalaya, especially class X students, namely there are still many who get unsatisfactory scores below average, this can be seen based on the average economic score based on the score data listed in the summative analysis data. The purpose of this study is to determine the difference in learning outcomes of students in economics subjects in experimental classes that use a TGT (Teams Games Tournamnet) type cooperative learning model with Question Card media on the initial measurement and final measurement in economics subjects regarding the concept of financial services institutions in the economy. The method used is an experimental method, with a research design using a Nonequivalent Control Group Design, as well as data collection techniques through multiple-choice tests (pretest and posttest). The population in this study is all class X at SMA Negeri 3 Tasikmalaya in the 2023/2024 school year which totals 433 students. The samples used were class X-10 with 36 people as an experimental class and class X-9 with 36 people as a control class with sampling using the purposive sampling technique. Based on the results of the study, it was shown that there was a difference in the improvement of learning outcomes of students in economics subjects in the experimental class that used the TGT (Teams Games Tournament) type cooperative learning model using Question Card media with a Sig. (2-tailed) value of 0.000, the control class that used conventional learning with a Sig. (2-tailed) value of 0.000 and the learning outcomes of the experimental class and the control class with a Sig value. (2-tailed) is 0.001, Ha is accepted if the value is Sig. (2-tailed) ≤0.05. Thus, it can be concluded that in this study Ha is accepted because there is an increase in student learning outcomes.